Identification With Additively Separable Heterogeneity. Issue 3 (20th May 2019) - Allen, Roy; Rehbeck, John
Abstract : This paper provides nonparametric identification results for a class of latent utility models with additively separable unobservable heterogeneity. These results apply to existing models of discrete choice, bundles, decisions under uncertainty, and matching. Under an independence assumption, such models admit a representative agent. As a result, we can identify how regressors alter the desirability of goods using only average demands. Moreover, average indirect utility ("welfare") is identified without needing to specify or identify the distribution of unobservable heterogeneity.